APPLYING CLEANER PRODUCTION STRATEGIES TO ACHIEVE GREEN HUMAN RESOURCE MANAGEMENT PRACTICES-A FIELD STUDY IN THE STATE COMPANY FOR DRUGS INDUSTRY AND MEDICAL APPLIANCES - Alaa Abdulsalam Mustafa (Scholars Digest Publishing, 2024)
Purpose: To identify cleaner production technology and its impact on the state company for drugs industry and medical appliances’ adoption of green human resources management practices. Design/ Methodology/ Method: A questionnaire form was developed to ensure the existence of a relationship between the research variables, and based on the comprehensive inventory method, (89) questionnaire forms were distributed in the state company for drugs industry and medical appliances, and their data were analyzed using the (SPSS V.24) program. Results: The research results showed that there is a knowledge gap related to determining the nature of the relationship between the application of cleaner production technology and green human resource management practices, and it was confirmed that there is a statistical relationship between the research variables. Therefore, the researched company needs to apply cleaner production technology to adopt green human resource management practices. Practical implications: The results of the research can be benefited by applying cleaner production technology to adopt green human resources management practices, thus increasing the company’s chances of achieving its goals and objectives. Originality/ value: This is the first research to combine current variables (cleaner production and green human resources management) in one hypothetical model. This means that there is no knowledge product that determines the relationship between these variables, whether at the level of Iraqi or other organizations, or at the level of Arab and foreign studies, so the current research came to fill that gap.
Keywords: cleaner production, green human resources management.